Silicon and the Plant Extracellular Matrix - Guerriero, Gea; Hausman, Jean-Francois; Legay, Sylvain (Frontiers in Plant Science, 2016)
Silicon (Si) is one of the most abundant elements on earth. Although not considered essential for the growth and development of higher plants, it is nonetheless known to increase vigour and to play protective roles. Its protective effects include for instance alleviation of (a)biotic stress damages and heavy metal toxicity. Si was shown to interact with several components of the plant cell walls in the form of silica (SiO2). In plants SiO2 promotes strengthening of the cell walls and provides increased mechanical support to the aerial parts. The relationship SiO2-plant cell wall has been well documented in monocots and pteridophytes, which are known Si accumulators, while much less is known on the interaction of Si with the cell walls of dicots. We here provide a concise up-to-date survey on the interaction between Si and plant cell wall components by focussing on cellulose, hemicelluloses, callose, pectins, lignin and proteins. We also describe the effects of Si on cell wall-related processes by discussing the published results in both monocots and dicots. We conclude our survey with a description of the possible mechanisms by which Si exerts priming in plants.